2014
DOI: 10.1002/anie.201402574
|View full text |Cite
|
Sign up to set email alerts
|

Facile One‐Pot, One‐Step Synthesis of a Carbon Nanoarchitecture for an Advanced Multifunctonal Electrocatalyst

Abstract: A one-pot/one-step synthesis strategy was developed for the preparation of a nitrogen-doped carbon nanoarchitecture with graphene-nanosheet growth on the inner surface of carbon nanotubes (CNTs). The N-graphene/CNT hybrids exhibit outstanding electrocatalytic activity for several important electrochemical reactions as a result of their unique morphology and defect structures, such as high but uniform nitrogen doping, graphene insertion into CNTs, considerable surface area, and the presence of iron nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 54 publications
(26 reference statements)
3
94
0
3
Order By: Relevance
“…In addition, the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Table 1 for comparison. [32][33][34][35][36][37][38][39][40][41][42] Clearly, N,P-GCNS is among the best bifunctional oxygen-electrode catalysts, showing great promise in the fields of rechargeable metal-air batteries and unitized regenerative fuel cells (URFC). respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Table 1 for comparison. [32][33][34][35][36][37][38][39][40][41][42] Clearly, N,P-GCNS is among the best bifunctional oxygen-electrode catalysts, showing great promise in the fields of rechargeable metal-air batteries and unitized regenerative fuel cells (URFC). respectively.…”
Section: Resultsmentioning
confidence: 99%
“…S16). Therefore, the presence of S could be beneficial for enhancing ORR activity [41,47,51]. Moreover, electrochemical impedance spectroscopy (EIS) (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…In this way, the doping step is simplified while the element utilization efficiency is improved. Moreover, the existence of nanoparticles such as Fe, FeS, and FeN 0.05 could further boost the ORR activity by tuning the redox properties of surrounding carbon layers embedded with active sites [51]. Consequently, the resulting PmPDA-GRFe catalyst exhibited prominent ORR activity as well as excellent long-term stability both in alkaline and acidic media, surpassing those of commercial Pt/C catalyst (20 wt% Pt, Johnson Matthey).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that Fe-containing species embedded in the carbon matrix exhibit enhanced catalytic activity for the ORR, such as iron nitrides, 29 iron carbides, 30-32 iron oxides 33,34 and metallic iron. 35,36 Recent study by Zhang et al reported a type of novel bifunctional catalyst used for the oxygen reduction and evolution reactions based on N and P dual-doped porous carbon nanosheets comprising uniform FeP nanoparticles (NPs) embedded in the carbon layers. 37 This provides a new idea for the application of iron phosphides in the ORR.…”
Section: Introductionmentioning
confidence: 99%